THE KINETIC AND DIFUSSION ION EXCHANGE OF Cs ON ZEOLITE BAYAH, LAMPUNG, AND TASIKMALAYA - Dian Anggraini; Noviarty Noviarty; Arif Nugroho (Institut Teknologi Bandung, 2010)
The ion exchange of Cs on NH4-Zeolite which has been activated become a zeolite monocation has been conducted on natural zeolite from Bayah, Lampung, and Tasikmalaya. On these three types of zeolite, the process of ion exchange of Cs with ammonium ion was conducted at various time (from 1 hour up to 24 hours) and temperature (303 K and 323 K). Cation exchange kinetics and diffusion process on each type of zeolite was observed and calculated the parameters included diffusion coefficient and activation energy using Arrhenius formula. The study showed that diffusion coefficient from Cs-ions into zeolite of Bayah, Lampung, and Tasikmalaya almost same, which is about 2,3 10-13, 2,3 10-13 and 2,1 10-13 m2.det.-1 at temperature 303 K, and 9,3 10-14, 9,6 10-14, and 9,6 10-14 m2.det.-1 at temperature 323 K. The parameter calculation result of ion exchange reaction is activation energy Ea (kJ/mol) on that types of zeolite are almost same value, which is 36.61, 36.61, and 31.09 for each zeolite of Bayah, Lampung, and Tasikmalaya. The study showed that Ea value was greater than the previous study by using artificial zeolite (zeolit-A with Ea = 9,96 kJ/mol), so it can be concluded that Cs-ions exchange into natural zeolite has a greater barrier because the composition of natural zeolite more complex which was might contain more than one types of zeolite structure.